Determination of microbiological (Staphylococci) quality of fast food sold in the different restaurant in Sylhet sadar (Research in Agriculture Livestock and Fisheries, 2018)
Fast food monger and restaurants premises are more rapidly growing in Sylhet city. This may cause serious health concern due to unhygienic environment are noticeable almost all types of fast food vendors and restaurants. Hence, the study was undertaken to assess a total viable bacterial count and especially emphasis given on total staphylococcal count of fast food items from various restaurants in and around Sylhet town. From January to February 2016, a total of 45 samples were collected and assessed of five fast food items (Singara, Shamucha, Chicken burger, Chicken roll and cake) belongs to three types of restaurants (Street, mid-level and high level). Assessment revealed, the highest mean value of TVC (Total Variable Count) was found in Shamucha (89.6×109 CFU/g.) nearly all types of restaurants whereas lowest was observed in Chicken burger (58.8×109 CFU/g.). However, Staphylococcal load (mean value of TSC) was seen highest in both Shamucha and Chicken burger (26×103 CFU/g.) and lowest were in cake (16×103 CFU/g.) of all types of restaurants. Street level restaurants were observed highly risk for microbial as well as Staphylococcal load when comparison with mid-level and high level restaurants. Based on International Microbiological Criteria, the total viable count and total staphylococcal count found in fast food samples were unsatisfactory of all types of restaurants. Therefore, this study recommends that further analysis is needed regarding this issue. Besides, necessary steps should be taken by the Government for maintaining hygienic standard for preparing, processing and handling cooked food in various restaurants.Res. Agric., Livest. Fish.5(3): 327-333, December 2018